CO2 methanation over the Ni-based catalysts supported on the hollow ZSM-5 zeolites: Effects of the hollow structure and alkaline treatment. (15th February 2023) - Cui, Yan; Chen, Bin; Xu, Leilei; Chen, Mindong; Wu, Cai-e; Qiu, Jian; Cheng, Ge; Wang, Ning; Xu, Jingxin; Hu, Xun
Graphical abstract: Highlights: The hollow ZSM-5 zeolites were synthesized by alkaline treatment of ZSM-5. The Ni-based catalysts supported on ZSM-5 with different hollow structures. The influence of hollow structure on Ni-based CO2 methanation catalyst was studied. The 15Ni/H-ZSM-5-T treated with TPAOH alkaline solution showed optimum performance. The reaction intermediates of CO2 methanation were studied by in-situ DRIFTS. Abstract: Hollow ZSM-5 zeolites prepared using different alkaline solutions were employed as Ni based catalyst supports for the methanation of CO2 . The catalysts were thoroughly characterized, and in-situ DRIFTS were used to study the CO2 methanation intermediates. Using the hollow Ni-based catalysts led to enhanced CO2 conversion as well as CH4 selectivity compared with the traditional Ni/ZSM-5, which was mainly due to the strong basicity of the hollow supports as well as the presence of silicon hydroxyls. Meanwhile, the 15Ni/H-ZSM-5-T catalyst prepared with TPAOH solution had higher catalytic performance than 15Ni/H-ZSM-5-NT and 15Ni/H-ZSM-5-N. The introduction of the hollow zeolite morphology led to enhanced diffusion behavior in the catalyst, which inhibited catalyst deactivation. Therefore, the hollow structure of the support with alkaline treatment was an important consideration for the design and preparation of high-performance Ni-based catalysts for CO2 methanation.